Kimura disease: a case series presenting as orbital mass - Mohd Ali, Razana; Ngan, Kah Wai; Awang Ahmad, Norashikin; Hussin, Huzlinda; A Rahim, Ruwaida (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2021)
Introduction: Kimura disease (KD) is a chronic inflammatory process that can occur within the head and neck region involving deep subcutaneous tissue. Tumour-like nodules were the usual presentations. Albeit rare, there have been reports on orbital KD occurrence in recent years. Case series: We reported seven cases of orbital KD of patients aged 12 to 67 years old from a tertiary referral center in Malaysia. Painless orbital swelling was the most common presentation. The duration of presentation ranges from 2 months up to 6 years. Peripheral blood investigations demonstrated eosinophilia (>5% of white blood cells) and elevated serum immunoglobulin E (IgE) level. The orbital mass measures from 1cm to 5cm in dimension. Differentials include Hodgkin lymphoma, haemangioma, angiolymphoid hyperplasia with eosinophilia (ALHE) or a pseudotumour. In all cases, surgical excision was performed. Histopathological examination showed various degrees of lymphoid hyperplasia with germinal centres, eosinophilic infiltrates, hyalinized vascular proliferation and fibrosis. Diagnoses of KD were made. There were no recurrences seen on available follow up data of 2 cases. Conclusion: Albeit rare, orbital KD alerts to its common existence within the head and neck region. It mimics ALHE microscopically and malignant neoplasm clinically and radiologically. Thus, awareness for this entity, its histological characteristics with clinical and radiological correlations are essential in achieving a correct diagnosis. As there is no consensus on its optimal treatment, and its unpredictable response to the therapeutic interventions, the choice and extent of treatments also varied according to individual response and disease recurrence.